O-228 The SSRI antidepressant Sertraline inhibits CatSper calcium channels in human sperm. (6th August 2021) - Rahban, R; Rehfeld, A; Schiffer, C; Brenker, C; Palme, D. Louise Egeberg; Wang, T; Lorenz, J; Almstrup, K; Skakkebaek, N E; Strünker, T; Nef, S
Abstract: Study question: Do Selective Serotonin Reuptake Inhibitor (SSRI) antidepressants affect the function of human sperm? Summary answer: The SSRI-antidepressant Sertraline (e.g. Zoloft) inhibits the sperm-specific Ca 2+ channel CatSper and affects human sperm function in vitro . What is known already: In human sperm, CatSper translates changes of the chemical microenvironment into changes of the intracellular Ca 2+ concentration ([Ca 2+ ]i ) and swimming behavior. CatSper is promiscuously activated by oviductal ligands, but also by synthetic chemicals that might disturb the fertilization process. It is well known that SSRIs have off-target actions on Ca 2+, Na +, and K + channels in somatic cells. Whether SSRIs affect the activity of CatSper is, however, unknown. Study design, size, duration: We studied the action of the seven drugs belonging to the most commonly prescribed class of antidepressants, SSRIs, on resting [Ca 2+ ]i and Ca 2+ influx via CatSper in human sperm. The SSRI Sertraline was selected for in-depth analysis of its action on steroid-, prostaglandin-, pH-, and voltage-activation of human CatSper. Moreover, the action of Sertraline on sperm acrosomal exocytosis and penetration into viscous media was evaluated. Participants/materials, setting, methods: The activity of CatSper was investigated in sperm of healthy volunteers, using kinetic Ca 2+ fluorimetry and patch-clamp recordings. Acrosomal exocytosis was investigated using Pisum sativum agglutinin (PSA) and image cytometry. Sperm penetration in viscous media was evaluated using the Kremer test. Main results and the role of chance: Four SSRIs increased [Ca 2+ ]i, two out of which also attenuated ligand-induced Ca 2+ influx via CatSper. In contrast, Sertraline decreased [Ca 2+ ]i and almost completely suppressed ligand-induced Ca 2+ influx via CatSper. Remarkably, the drug was about four-fold more potent to suppress prostaglandin- versus steroid-induced Ca 2+ influx. Sertraline also suppressed alkaline- and voltage-activation of CatSper, indicating that the drug directly inhibits human CatSper. Finally, Sertraline suppressed ligand-induced acrosome reaction and sperm penetration into viscous media. Limitations, reasons for caution: This is an in vitro study. Future studies have to assess the physiological relevance in vivo . Wider implications of the findings: The off-target action of Sertraline on CatSper in human sperm might impair the fertilization process. In a research setting, Sertraline may be used to selectively inhibit prostaglandin-induced Ca 2+ influx. Trial registration number: CRU326